2014
DOI: 10.5888/pcd11.130231
|View full text |Cite
|
Sign up to set email alerts
|

Menu-Labeling Usage and Its Association with Diet and Exercise: 2011 BRFSS Sugar Sweetened Beverage and Menu Labeling Module

Abstract: IntroductionThe primary objective of our study was to investigate the association between menu-labeling usage and healthy behaviors pertaining to diet (consumption of fruits, vegetables, sodas, and sugar-sweetened beverages) and exercise.MethodsData from the 2011 Behavioral Risk Factor Surveillance System, Sugar Sweetened Beverage and Menu-Labeling module, were used. Logistic regression was used to determine the association between menu-labeling usage and explanatory variables that included fruit, vegetable, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
1
9
1
Order By: Relevance
“…The findings showed a somewhat higher prevalence of menu labeling use than previous studies in single jurisdictions 14,23 and multiple jusrisdictions. 11,15 A 2010 study among 1,083 customers from King County, Washington, showed that while 60% of customers reported seeing menu labeling, only about 25% reported using it. 14 Another study with 8,489 adult customers from New York City in 2009 showed that only 15% of customers reported using calorie information after 9 months of full enforcement of menu labeling, though the researchers did not specify whether or not customers noticed or saw menu labeling.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings showed a somewhat higher prevalence of menu labeling use than previous studies in single jurisdictions 14,23 and multiple jusrisdictions. 11,15 A 2010 study among 1,083 customers from King County, Washington, showed that while 60% of customers reported seeing menu labeling, only about 25% reported using it. 14 Another study with 8,489 adult customers from New York City in 2009 showed that only 15% of customers reported using calorie information after 9 months of full enforcement of menu labeling, though the researchers did not specify whether or not customers noticed or saw menu labeling.…”
Section: Discussionmentioning
confidence: 99%
“…11 Weight status was classified into three categories based on participants’ body mass index (BMI) using self-reported height and weight data: underweight/normal weight (BMI <25.0 kg/m 2 ); overweight (BMI 25.0–29.9 kg/m 2 ); and obese (BMI ≥30.0 kg/m 2 ). 21 The weight status categories of underweight and normal weight were combined as a single category because <2% of participants were classified as underweight.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Menu labeling, the practice of providing nutritional information of calories, carbohydrates, fat, sodium, and other selected nutrients in menu items at points of purchase, has recently been regarded as an important strategy in the effort to reduce the prevalence of obesity in the United States (Krieger & Saelens, 2013). Several states and cities in the United States have passed regulations requiring restaurants to post nutrition labeling (Bowers & Suzuki, 2014). In 2010, U.S. federal legislation was enacted to encourage healthy menu selections through the Patient Protection and Affordable Care Act (PPACA), which requires restaurant chains to post caloric content and other nutritional facts of menu items (Patient Protection and Affordable Care Act, 2010;Peregrin, 2010).…”
Section: Introductionmentioning
confidence: 99%